Tannic acid as a binder and electronic conductor precursor in silicon electrodes for Li-ion batteries - Nassima Kana; Sarah Olivier-Archambaud; Thomas Devic; Bernard Lestriez (Electrochemistry Communications, 2023)
State of-the-art Si electrodes for Li-ion batteries typically require the addition of an advanced polymeric binder and a conductive carbon additive to the active material in order to circumvolve the issues associated with silicon, namely its poor conductivity in the oxidized state, and its high volume variation upon lithiation which give rise to several failure mechanisms. Here, we demonstrate that both additives can be replaced by a cheap, naturally available, polyphenol, tannic acid (TA). We show that Si/TA electrodes (80/20 wt%), even with a high loading (∼2 mg_Si cm−2), can retain a specific capacity above 2000 mAh g−1 after 50 cycles. This unexpected result appears to result from the irreversible reduction of TA during the first cycle, into a conducting, likely polymeric, species.